Engineering mesoporous silica microspheres as hyper-activation supports for continuous enzymatic biodiesel production. (8th July 2019) - Kalantari, Mohammad; Yu, Meihua; Liu, Yang; Huang, Xiaodan; Yu, Chengzhong
Abstract : Engineered mesoporous silica materials shows promising potential for continuous biodiesel production. Abstract : Synthesizing hydrophobic nano-supports to induce hyper lipase activity has been extensively studied for enzymatic biodiesel production. However, their practical applications are hindered by the drawback of high mass transfer hindrance. Designing support materials to integrate hyper-activated lipase into practical biodiesel production systems represents a major challenge for industrial enzymatic catalysis. Here, we report the preparation of functionalized mesoporous silica microspheres (MSMs) as hyper-activation lipase (from Candida rugosa ) supports for continuous enzymatic biodiesel production. The functionalized alkyl chain length and lipase loading amount of MSMs have been optimized to deliver a high hyper enzymatic activity (1.14 times that of free lipase). When applied as a catalyst in a prototype transesterification reactor, a high initial conversion (99%) and excellent stability (64% of initial conversion after 24 h) have been demonstrated, superior to other lipase catalysts used in biodiesel production reactors. The new catalyst and the material engineering strategy developed here shed new light on designing enzyme supports for biocatalytic applications.